3D hydrogel mimics of the tumor microenvironment: the interplay among hyaluronic acid, stem cells and cancer cells. (16th November 2020) - Amorim, Sara; Soares da Costa, Diana; Pashkuleva, Iva; Reis, Celso A.; Reis, Rui L.; Pires, Ricardo A.
Abstract : A 3D tumor microenvironment model is presented, combining hyaluronic acid (HA) and alginate. The model can be used to mimic the bioactivity of HA in gastric cancer, as well as the crosstalk between cancer cells and mesenchymal stem cells. Abstract : The present work reports on a 3D model of the tumor microenvironment that contains hyaluronic acid (HA) and alginate, and demonstrates the utility of this model to study the effect of HA size on the crosstalk between cancer cells and mesenchymal stem cells (MSCs). The system incorporates a core that contains HA of specific size ( i.e. 6.4, 741 or 1500 kDa) with encapsulated epithelial MKN45 cancer cells and a shell with MSCs that mimic the presence of stem cells next to the tumor site. It was found that short HA ( i.e. 6.4 kDa) promotes the invasion of cancer cells from the core to the shell, whereas longer HA ( i.e. 741 and 1500 kDa) recruits the MSCs into the core, i.e. the tumor site, where a reduction of the formation of cancer cell aggregates was observed. In summary, the developed 3D model recapitulates some key tumor features related to the effect of HA size on both cancer cell invasiveness and MSC behavior at the tumor site.